Математичне комп’ютерне моделювання квантово-механічних явищ та процесів - Сосницька, Наталя Леонідівна; Сосницкая, Наталья Леонидовна; Sosnytska, Natalia; Морозов, Микола Вікторович; Морозов, Николай Викторович; Morozov, Mykola; Халанчук, Лариса Вікторівна; Халанчук, Лариса Викторовна; Khalanchuk, Larysa (Мелітополь: ТДАТУ, 2020)
UK: У статті розглянуто застосування математичного комп’ютерного моделювання стану електронів у просторовій квантовій ямі з нескінченно високими стінками. Використано хвильове рівняння Шредінгера для стаціонарних станів електрона і граничні умови для отримання власних значень енергії та виду хвильової функції і щільності ймовірності. Для аналітичного розв’язку рівняння Шредінгера використовується метод Фур’є розділення змінних. Для побудови графіків хвильової функції та щільності ймовірності знаходження електрону в заданій області квантової ями використано пакети програм Scilab, MathCad, дискретні моделі розв’язку диференціальних рівнянь у частинних похідних та дискретні структуровані сітки. RU: В статье рассмотрено применение математического компьютерного моделирования состояния электронов в пространственной квантовой яме с бесконечно высокими стенками. Использовано волновое уравнение Шредингера для стационарных состояний электрона и граничные условия для получения собственных значений энергии, вида волновой функции и плотности вероятности нахождения электрона в заданной области квантовой ямы. Для аналитического решения уравнения Шредингера используется метод Фурье разделения переменных. Для построения графиков волновой функции и плотности вероятности нахождения электрона в заданной области квантовой ямы использованы пакеты программ Scilab, MathCad, дискретные модели решения дифференциальных уравнений в частных производных и дискретные структурированные сетки. EN: The article deals with the application of mathematical computer simulation of the state of electrons in a spatial quantum well with infinitely high walls. Mathematical computer simulation methods were used to study and research the wave function of an electron and the eigenvalues of energy and their dependence on the structure, shape and size of a quantum dot. We used the Schrödinger wave equation for steady state electrons and boundary conditions to obtain the eigenvalues of the energy and the type of wave function and probability density of finding an electron in a given quantum well. The analytical solution of the Schrödinger equation uses the Fourier method of separating variables. Using the Fourier method of separation of variables, the boundary conditions and the numerical method of successive approximations (iterations) determine the eigenvalues of energy and wave numbers. Scilab, MathCad software package, discrete partial differential equation models, and discrete structured grids were used to plot the wave function and the probability density of finding an electron in a given quantum well. Using the Scilab software package, you can visualize the kind of wave function and probability density for a 3D spatial quantum well. The results of the research were used to provide methodological support for the laboratory practicum in the following disciplines: physics, physical foundations of modern information technologies and physico-mathematical provision of master's programs in the study of sections "Zone theory of solids" and "Electronic conductivity of metals".
Математическое компьютерное моделирование квантово-механических явлений и процессов
Mathematical computer simulation of quantummechanical phenomena and processes
Keywords: математичне комп’ютерне моделювання; рівняння Шредінгера; квантові точки; хвильова функція; власні значення енергії електрона; структуровані дискретні моделі; віртуальні імітаційні лабораторні роботи; математическое компьютерное моделирование; уравнение Шредингера; квантовые точки; волновая функция; собственные значения энергии электрона; структурированные дискретные модели; виртуальные имитационные лабораторные работы; mathematical computer simulation; Schrödinger equation; quantum dots; wave function; eigenvalues of electron energy; structured discrete models; virtual simulation laboratory works